Ground improvement case histories embankments with special reference to consolidation and other physical methods - Indraratna, Buddhima; Chu, Jian 1963-; Rujikiatkamjorn, Cholachat (Butterworth Heinemann, 2014)
Written by a group of international contributors, Ground Improvement Case Histories: Embankments with Special Reference to Soil Consolidation and Other Physical Methods, employs the use of case-histories to illustrate and apply equations, numerical methods and technology to undertake even the most complicated ground improvement projects. In this book, each case-history provides an overview of the specific technology followed by field applications and in some cases comprehensive back-analysis through numerical modelling. Specific embankment case-histories with special reference to soil consolidation included are: Ballina Bypass (Australia), Tianjin Port (China), Second Bangkok International Airport (Thailand), Changi East reclamation (Singapore), Maizuru-Wakasa Expressway (Japan) and Colombo Airport Expressway, Sri Lanka. Other physical methods include performance of stone columns at Penny’s Bay reclamation in Hong Kong and PCC piles for highway and high-speed railway construction in China, among others.--Provided by publisher.